Body Posture Evaluation of Dental Specialty Groups and Risk of Developing Musculoskeletal Disorders - Jahanimoghadam, Fatemeh; Hasheminejad, Naimeh; Hashemi-Nejad, Naser (Journal of Dentistry Indonesia, 2021)
Objective: Adopting correct body postures is extremely essential in preventing future musculoskeletal disorders in Dentists. The aim of this study was to evaluate the body posture of general and specialist dentists to find awkward body postures, badly postured body parts and the risk of developing future MSDs. Methods: Stratified sampling method was used to recruit 224 dentists in Kerman and Mashhad. The most frequently adopted body posture was selected and based on Rapid Entire Body Assessment (REBA) method, scores were given to the angulation of different body parts. T-test and ANOVA test were performed to analyze the data. Results: About 10% of dentists had a REBA score which showed a high or very high risk of developing MSDs. Specialists and general dentists were not different in terms of REBA score. Among different specialties, periodontists had the highest REBA score. Overall, forearms and neck had the highest REBA score. Conclusion: General dentists and all dental specialties (except operative dentists) were at moderate risk of developing MSDs. Periodontists were at higher risk of developing MSDs. Based on REBA, the forearm and the neck were the most badly postured body parts.